Where the rivers merge : a novel - Monroe, Mary Alice (New York, NY : William Morrow, 2025)
Spanning eight decades in South Carolina's Lowcountry, Eliza Rivers fights against societal constraints, war, and family strife to protect her beloved estate, Mayfield, but as she nears the end of her life, she must make one final stand to secure its future.
Keywords: Families -- Fiction; Conservation easements -- Fiction; South Carolina -- Fiction; Domestic fiction; Bildungsromans; Novels